Eco-Friendly Synthesis of CuO Nanoparticles by Using Ulva Fasciata Algae Extract for Antibacterial and Supercapacitor Application - Balasubramanian, R.; Ravi , S. (International Journal of Membrane Science and Technology, 2023)
An eco-friendly, biogenic synthesis of copper oxide nanoparticles (CuO NPs) using ulva fasciata extract was reported. XRD, FTIR, UV-Vis spectroscopy, SEM, TEM, EDX, antibacterial activity and electrochemical analysis were used to characterize the biosynthesized CuO NPs. XRD spectrum reveals the monoclinic structure. The FTIR spectrum confirms the functional group of CuO NPs. The optical study gives the band gap values of CuO at different concentrations of ulva fasciata algae extract. The antibacterial activities were tested against one gram-positive bacteria S. aureus and one gram-negative bacteria E. coli. The CV curve exhibits a high specific capacitance of 132 F/g, at the scan rate of 10 mV/S.